ANALISIS KELAYAKAN INVESTASI PEMBUATAN ASPHALT MIXING PLANT (AMP ) STUDI KASUS PADA PT.CA - , Ni Gusti Putu Kurniawati, SE, Dr. Hardo Basuki, M.Soc., Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
To support the development in South Kalimantan Province including to enhance the growth of oil palm tress and coal minning available now, it is required to provide with proper infrastructure. To accomplish such purpose, it is required to develop an Asphalt Mixing Plant (AMP) properly. The vast improvement of the development of the infrastructure make the need of hotmix increased too, therefore the investors are interested in investing their capital in the business of Asphalt Mixing Plant. The purpose of this thesis research is to determine and analyze the investment feasibility of PT. CA. This research use both qualitative and quantitive research is conducted by capital budgeting method through the Benefit Cost Ratio, NPV, Payback period and IRR which are based on the cash flow projection. From the project feasibility analysis of the proposed AMP a total investment Rp.14.601.648.000,- Is needed and applying financial and economic analysis, it is found out that BCR = 1.76 value is a little above 1.00, NPV = Rp. 25.759.064.428,- , IRR = 43.4% and the PP is 37 months therefore. From the research it is gathered that the NPV, Payback Periode, IRR and PI all showed that they are feasible for the bank financing, and that in the cash flow projection the company is capable of paying the credit repayment to the bank. Sensitiveness analysis needed to give an alternative consideration for several main factors on cash flow. Sensitiveness analysis is carried for the change of sales, cost and interest rate. From several main factor, increase of cost is the most sensitive, it means the increase period allowed for cost is 40 percents, therefore the investment no propered. Second of sensitiveness analysis is decrease of sales, if decrease at the mount of 40 percents, therefore the investment no propered. And the least sensitive is interest rate, if increase at the amount of 50 percents, the investment still propered.